Oxygen delivery is not a limiting factor during post-exercise recovery in healthy young adults - Robert T. Mankowski; Victor M. Niemeijer; Jasper P. Jansen; Lotte Spraakman; Henk J. Stam; Stephan F.E. Praet (Elsevier, 2017)
Purpose: It is still equivocal whether oxygen uptake recovery kinetics are limited by oxygen delivery and can be improved by supplementary oxygen. The present study aimed to investigate whether measurements of muscle and pulmonary oxygen uptake kinetics can be used to assess oxygen delivery limitations in healthy subjects. Methods: Sixteen healthy young adults performed three sub-maximal exercise tests (6 min at 40% Wmax) under hypoxic (14%O2), normoxic (21%O2) and hyperoxic (35%O2) conditions on separate days in randomized order. Both Pulmonary VO2 and near infra red spectroscopy (NIRS) based Tissue Saturation Index (TSI) offset kinetics were calculated using mono-exponential curve fitting models. Results: Time constant τ of VO2 offset kinetics under hypoxic (44.9 ± 7.3s) conditions were significantly larger than τ of the offset kinetics under normoxia (37.9 ± 8.2s, p = 0.02) and hyperoxia (37±6s, p = 0.04). TSI mean response time (MRT) of the offset kinetics under hypoxic conditions (25.5 ± 13s) was significantly slower than under normoxic (15 ± 7.7, p = 0.007) and hyperoxic (13 ± 7.3, p = 0.008) conditions. Conclusion: The present study shows that there was no improvement in the oxygen uptake and muscle oxygenation recovery kinetics in healthy subjects under hyperoxic conditions. Slower TSI and VO2 recovery kinetics under hypoxic conditions indicate that both NIRS and spiro-ergometry are appropriate non-invasive measurement tools to assess the physiological response of a healthy individual to hypoxic exercise.